XITOY MANBALARIDA DAVAN DAVLATINING SHAKLLANISH JARAYONI - Toyirov Sheralixon, Sheraliyev Bayramali (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The article is dedicated to the study of the formation process of the Davan state. The Davan state existed in Central Asia and Eastern Turkestan in the 6th-7th centuries, and the article analyzes its formation, political, social, and economic aspects. It explores the early stages of the Davan state, its significance, and its relations with other states. The history of the Davan state, its governance, foreign policy, and cultural development processes, as well as the general political landscape of the time, are discussed. Additionally, the article examines the impact of the Davan state on other political systems in Central Asia and its unique characteristics.